Difficulties Related to the Communication with the Patient with Aphasia According to the Nursing Staff - Małgorzata Cheba; Regina Żuralska; Marcelina Skrzypek-Czerko (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Sudden onset of aphasia due to stroke deprives man of communication with the environment, as well as eliminates of family, social and professional life. Difficulties in communication with patients with aphasia are important issues in ensuring the proper care and improve the quality of patients’ life. Therefore, it is important to have the nursing staff knowledge and skills in communication with a patient with aphasia. Aim. The aim of the study was to evaluate the difficulty of communication with a patient with aphasia, to determine the possibility of communication and the factors contributing to the improvement of the situation of the patient in the opinion of the nursing staff. Material and Methods. The survey was conducted among 100 nurses working on the neurological wards in six specialized hospitals in the Pomerania region, between August 2012 to August 2013. Research material was collected by the author’s questionnaire. Results. Statistical analysis revealed that age, education and work experience of nurses are related to owned by nurses the knowledge and skills to overcome communication difficulties. Conclusion. Better educated nurses with long work experience, often declare their readiness to therapeutic cooperate with patient with aphasia. Most respondents indicated that no therapeutic action by nurses result of external causes that relate to exess duties. (JNNN 2014;3(2):75–80)